Unravelling the transition from vegetative to reproductive stages using Passiflora organensis as a model plant - Moraes, Tatiana de Souza (2020)
The genus Passiflora is an excellent model for phase transition studies, because there are obvious morphological differences between plants in the juvenile, adult vegetative, and adult reproductive stages. In almost all species of the genus Passiflora, plants in the juvenile stage produce leaves with different morphology from the adult plants, and do not produce tendrils. On the other hand, plants in the adult vegetative stage develop tendrils at the leaf axils, and in the adult reproductive stage plants produce from the axillary meristems, tendrils and flowers, simultaneously. The proteins belonging to the FT/TFL1 family are important regulators of the phase transition process and need to interact with specific transcription factors to perform their biological functions. The basic region/leucine zipper (bZIP) and the teosinte branched1/ cycloidea/ proliferating cell factor (TCP) transcription factor (TF) families, which contain key players of plant development, are two families of genes encoding proteins that form unique complexes with FT/TFL1. The product of the FLOWERING LOCUS T (FT) gene is considered as the florigen agent and interacts with the bZIP protein FLOWERING LOCUS D (FD), resulting in the induction of flowering by activating transcription of genes involved in floral meristem identity, such as LEAFY (LFY) and APETALA1 (AP1). In addition, literature reports reveal that in some species, the proteins encoded by the FT and bZIP transcription factors interact with 14-3-3, a highly conserved scaffold protein, resulting in the formation of a hexameric protein complex. This complex plays a critical role in flowering time control, being designated as the florigen activation complex (FAC). Moreover, some proteins belonging to the TCP family may interact with FT protein, as well as with the product of its paralog TWIN SISTER OF FT (TSF), modulating their activity in the axillary buds to repress the premature floral transition of axillary meristems. In Passiflora species the molecular mechanisms involved in the vegetative-reproductive phase transition are basically unknown. Thus, this work aims to elucidate the mechanisms involved in the phase transition process during the development of Passiflora organensis, focusing on the transition to flowering. Then, with the use of appropriate developmental study tools, including light and electron microscopy, associated with gene expression analysis and protein-protein interaction techniques, the present work (a) morphologically characterized the transition from vegetative to reproductive phases in Passiflora organensis, (b) identified and characterized the gene structure of LFY and AP1 genes as well as FT/TFL1, bZIP, TCP and 14-3-3 gene families in Passiflora organensis, (c) characterized the expression pattern of the FT/TFL1 gene family, LFY, and AP1 by qRT-PCR and in situ hybridization analysis, (d) validated the activity of proteins encoded by genes belonging to FT/TFL1, bZIP, TCP and 14-3-3 families by yeast two-hybrid assay, and (e) performed heterologous functional analyzes by overexpression of the Passiflora organensis genes PoFT, PoTSFa, PoTFL1, PoBFT, PoATC, and PoMFT in the model plant Arabidopsis thaliana. The results of this work are fundamental to conclude the characterization of the activity of these genes in Passiflora organensis and will be important for selecting the right genes to focus on future research and for applications in studies of yield increase in Passiflora species with commercial interest, such as passionfruit